HSCs/MPPs as cells of origin with altered differentiation hierarchy impairing immunomicroenvironment in PML::RARA and CBFα/β fusion AML - Niu Qiao; Zi-Xuan Wang; Yu-Liang Zhang; Liu-Qing-Qing Zhang; Hong-Ming Zhu; Xiang-Qin Weng; Yong-Mei Zhu; Wen-Yan Cheng; Jian-Feng Li; Lu Jiang; Xiao-Yu Yan; Guang Yang; et al. (Proceedings of the National Academy of Sciences, 2026)
The theoretical possibility for leukemia stem cells (LSCs) to produce both leukemia blasts and dysfunctional immune cells remains underexplored. Here, we investigate three major fusion transcription factor (fTF)-driven acute myeloid leukemia (AML) subtypes [ RUNX1(CBFα)::RUNX1T1 , PML::RARA , and CBFB::MYH11 ] using two optimized single-cell RNA-sequencing technologies to trace fTF expression in 24 de novo AML patients. We demonstrate that the fTFs are widely expressed not only in leukemia blasts but also in differentiated myeloid and lymphoid cells, indicating hematopoietic stem cells or multipotent progenitors (HSCs/MPPs) as LSCs that propagate altered cellular differentiation hierarchies, including immune cells. DNA-FISH confirms the presence of fTFs in T lymphoid and erythroid cells, and targeted sequencing of secondary mutations in sublineages of cells corroborates hierarchical and stepwise leukemogenesis. By tracking RUNX1::RUNX1T1 -expressing cells in patients with or without relapse post–frontline chemotherapy, we highlight the necessity of eradicating LSCs to achieve sustained long-term complete remission and restore a functional immune system capable of suppressing residual disease over time. Comparative single-cell transcriptome analyses further reveal that fTFs are associated with AML subtype-specific differentiation defects in both innate and adaptive immune compartments, suggesting an altered landscape of immune cell–cell communication networks that may facilitate the survival and proliferation of leukemic blasts. Through the examination of intercellular communications among various putative fTF + and normal cell populations, we developed a ligand–receptor (L–R)-based risk-scoring model with independent prognostic value. Collectively, these findings provide insights into the cells of origin of LSCs and the implications of fTF expression for the immune landscape of AML.